(untitled) (Research, Society and Development, 2026)
Population aging is a global phenomenon that poses challenges related to the health and quality of life of older adults. In this context, strength training emerges as an effective intervention to promote active aging, mitigating the negative impacts associated with loss of muscle strength, functional mobility, and aging-related health conditions such as sarcopenia and risk of falls. The main objective was to analyze the impact of strength training on the quality of life in older adults, emphasizing its effects on muscle strength, functional mobility, mental health, and emotional well-being. The study was based on an integrative literature review, covering articles published between 2024 and 2026, available in academic databases such as PubMed, Scielo, and Google Scholar. Eleven studies were selected that addressed the impact of strength training on physical and psychological variables in older adults. The analyzed studies indicated that strength training provides significant benefits for muscle strength, balance, functional mobility, and bone density, in addition to reducing the risk of falls and sarcopenia. Additional benefits included improvements in mental health, such as reductions in psychopathologies, enhanced cognitive capacity, and greater emotional well-being. Strength training also demonstrated effectiveness in managing chronic pain and promoting autonomy in older adults. Furthermore, access to strength training programs should be expanded through public policies that ensure their inclusion as part of health strategies for the elderly.